THE REFORMS OF A.N. KASIGIN AND THEIR IMPLEMENTATION IN THE AGRICULTURE OF UZBEKISTAN (Scientific journal of the Fergana State University, 2025)
In history, the program known as the "Kasigin Course," recognizing the leading role of industry in production, proposes a refined and comprehensive system for the integrated economic uplift of the national economy. The impact of these reforms on the agricultural sector of Uzbekistan has led to a series of changes in the industry, opening new directions and opportunities. This article explores the process of implementing these reforms in agriculture.